Benefit of left atrial appendage electrical isolation for persistent and long-standing persistent atrial fibrillation: a systematic review and meta-analysis. Issue 8 (12th January 2018) - Romero, Jorge; Michaud, Gregory F; Avendano, Ricardo; Briceño, David F; Kumar, Saurabh; Carlos Diaz, Juan; Mohanty, Sanghamitra; Trivedi, Chintan; Gianni, Carola; Della Rocca, Domenico; Proietti, Riccardo; Perrotta, Laura; et al.
Abstract: Aims: The long-term outcomes of left atrial appendage electrical isolation (LAAEI) in patients with non-paroxysmal atrial fibrillation (AF) have corroborated the significant role of the LAA in this arrhythmia. We sought to investigate the incremental benefit of LAAEI in patients undergoing catheter ablation for persistent AF or long-standing persistent AF (LSPAF). Methods and results: A systematic review of Medline, Cochrane, and Embase for all the clinical studies in which assessment LAAEI in non-paroxysmal AF patients was performed. The benefit of LAAEI in patients with AF was analysed from seven studies that enrolled a total of 930 patients [mean age 63 ± 5 years; male: 69%]. All studies included patients with either persistent AF or LSPAF or the combination of them. The overall freedom from all-arrhythmia recurrence at 12 months of follow-up off antiarrhythmic medications in patients who underwent LAAEI was 75.5% vs. 43.9% in those in whom only standard ablation was performed [56% relative reduction and 31.6% absolute reduction; risk ratio (RR) 0.44, 95% confidence interval (95% CI) 0.31–0.64; P < 0.0001]. The rate of ischaemic stroke in the LAAEI group was 0.4% and in the control group 2.1% at 12 months follow-up (RR 0.40, 95% CI 0.12–1.30; P = 0.13). Acute complications rates were identical between groups [LAAEI 5.5%, control 5.5% (RR 0.99, 95% CI 0.46–2.16; P = 0.99)]. Conclusion: Left atrial appendage electrical isolation in addition to standard ablation appears to have a substantial incremental benefit to achieve freedom from ALL atrial arrhythmias in patients with persistent AF and LSPAF without increasing acute procedural complications and without raising the risk of ischaemic stroke.